2014
DOI: 10.18267/j.pep.496
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of VAT Gap in EU

Abstract: Abstract:This paper explains the term "VAT gap", and briefl y describes the calculation methods used in existing literature quantifying the VAT gap in various countries of the world. The VAT gap is calculated as the difference between the theoretical VAT liability ascertained from the national accounts and the VAT revenues accrued by the fi nancial authorities. Although VAT gap is not caused by tax evasion only, it could serve as its indicator. Further, it provides a review of scientifi c papers and various st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 5 publications
6
32
1
5
Order By: Relevance
“…In addition to previous empirical research studies [1,2,15,16,42,43], the present empirical research realized and found other specific quantitative and qualitative factors to be relevant in the perception of the efficiency of the tax system in Slovakia. The results of the extensive study were partially consistent with findings from other authors worldwide [9,33,[35][36][37][38] and also in Czech Republic and Slovakia [42,43,47]. However, the researchers specific research focus pointed to some aspects that were critical and unique for Slovakia.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…In addition to previous empirical research studies [1,2,15,16,42,43], the present empirical research realized and found other specific quantitative and qualitative factors to be relevant in the perception of the efficiency of the tax system in Slovakia. The results of the extensive study were partially consistent with findings from other authors worldwide [9,33,[35][36][37][38] and also in Czech Republic and Slovakia [42,43,47]. However, the researchers specific research focus pointed to some aspects that were critical and unique for Slovakia.…”
Section: Discussionsupporting
confidence: 65%
“…However, the researchers specific research focus pointed to some aspects that were critical and unique for Slovakia. Based on this empirical research conducted in Slovakia, it could be stated that there were different factors, which determined the perception of efficiency of the tax system in Slovakia when compared to other domestic or foreign research studies [1,15,16,33,[35][36][37][38]42,43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theory of national accounts provides the way for improvement of VAT taxation based on the estimate of statistical tax rates; the latter equal current tax rate multiplied by the share of goods (services) that require export compensation in GDP. «Input-output» balance approach to calculation of VAT can be used for the analysis of compliance with contemporary legislation, and minimization of cases of tax fraud and valuation of tax deductions [37].…”
Section: Resultsmentioning
confidence: 99%
“…Daňová mezera je měřena ve dvou krocích. Jak uvádí Zídková (2014), nejprve se určí teoretická DPH povinnost (zahrnující povinnost podle litery a ducha zákona) a poté se od takto zjištěné povinnosti odečte skutečně finančními autoritami (na akruálním principu) vybraná daň.…”
Section: úVodunclassified